Dampak Kepuasan Kerja Terhadap Kinerja Individual Di Bagian Administrasi - Yuli Endang; Rika Kusuma (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
This research aims to explore the relationship between job satisfaction and individual performance in administration. This study was conducted in a government administration department environment. Through analysis of survey and interview data, this research assesses the impact of job satisfaction on individual performance by considering the public administration context. The findings from this research can provide valuable insights for management to improve individual performance in the administrative environment.